413 ABO Blood Type and Thromboembolic Complications After Intracerebral Hemorrhage. (1st April 2022) - Ironside, Natasha; Chen, Ching-Jen; Connolly, E. Sander; Roh, David
Abstract : INTRODUCTION: Thromboembolic complications (TECs) are preventable causes of morbidity and mortality in patients with intracerebral hemorrhage (ICH). METHODS: Consecutive adult ICH patients enrolled in the Intracerebral Hemorrhage Outcomes Project with available ABO blood type data were included. The primary analysis dichotomized patients by O blood type status (O versus non-O cohorts). The primary outcome was TEC, comprising pulmonary embolism, deep venous thrombosis, ischemic stroke, and myocardial infarction, during the hospital stay. Outcomes were compared between cohorts using multivariable regression and propensity score-matched analyses. A secondary analysis compared outcomes between individual non-type O (i.e., A, B, and AB) and type O blood phenotypes. RESULTS: Type O and non-type O cohorts comprised 269 and 244 patients, respectively. TECs were more common in the type O cohort compared to non-type O cohort (15.2% vs. 9.4%; OR = 1.728 [1.004-2.974], p = 0.048). In the propensity score-matched analysis, comprising 126 patients in each cohort, TEC rates were comparable between the two matched cohorts (13.5% vs. 11.1%; OR = 1.248 [0.586-2.654], p = 0.566). TEC rates were also comparable between individual non-type O and type O blood phenotypes in the secondary analysis. Type A blood phenotype was associated with a lower modified Rankin Scale score at 90 days in shift analysis (OR = 0.654 [0.434-0.985], p = 0.042). CONCLUSION: ABO blood phenotype does not appear to be associated with TECs after spontaneous ICH. Type A blood phenotype may be associated with a better 90-day functional outcomes after ICH. A multicenter, multiethnic ICH study capturing genetic and molecular patient data may help elucidate the potential role of blood phenotype in ICH pathophysiology.